2010
DOI: 10.1593/tlo.10178
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the C-C Chemokine Receptor 7 Mediates Metastasis of Breast Cancer to the Lymph Nodes in Mice

Abstract: C-C chemokine receptor 7 (CCR7) controls lymphocyte migration to secondary lymphoid organs. Although CCR7 has been implicated in targeting the metastasis of cancers to lymph nodes, the role of CCR7 in the metastasis of breast cancer, along with the molecular mechanisms that are controlled by CCR7 that target breast cancer metastasis to the lymph nodes, has yet to be defined. To explore the cellular and molecular mechanisms of breast cancer cell migration to the lymph nodes, we used the mouse MMTV-PyVmT mammary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
67
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 25 publications
8
67
0
Order By: Relevance
“…In this sense, CCR7 recruits naive T-cells and dendritic cells to LNs, where they engage with each other and initiate adaptive immune responses [43]. In addition, studies have shown a significant correlation between CCR7 expression and LN metastasis [44]. Although other receptors may be involved in trafficking of IS BM Gr-1 + CD11b + cells to LNs, the expression of CCR7 may be sufficient in itself because new expression of CCR7 has been described as enough to induce metastasis to LNs in several human and mouse breast tumour cell lines [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, CCR7 recruits naive T-cells and dendritic cells to LNs, where they engage with each other and initiate adaptive immune responses [43]. In addition, studies have shown a significant correlation between CCR7 expression and LN metastasis [44]. Although other receptors may be involved in trafficking of IS BM Gr-1 + CD11b + cells to LNs, the expression of CCR7 may be sufficient in itself because new expression of CCR7 has been described as enough to induce metastasis to LNs in several human and mouse breast tumour cell lines [44].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have shown a significant correlation between CCR7 expression and LN metastasis [44]. Although other receptors may be involved in trafficking of IS BM Gr-1 + CD11b + cells to LNs, the expression of CCR7 may be sufficient in itself because new expression of CCR7 has been described as enough to induce metastasis to LNs in several human and mouse breast tumour cell lines [44]. It remains for future studies to identify which chemokines are increased in LNEs from IS mice.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous chemokines have been shown to promote cellular behaviors associated with breast tumor metastasis, including cell migration, increased expression and activity of matrix metalloproteinases (MMPs), increased heparanase activity, and invasion (412). Expression of chemokine receptors such as CXCR4 and CCR7 in tumor cells has also been linked to the dissemination of breast cancer cells to secondary organ sites that express high levels of their respective ligands (12,13). In addition to chemokine receptors, several other types of GPCRs, including protease-activated receptor-1 (PAR1), lysophosphatidic acid (LPA), and prostaglandin (EP) receptors, have been implicated in breast cancer metastasis (1418).…”
Section: Introductionmentioning
confidence: 99%
“…In breast carcinogenesis it has been attributed a number of potential functions, including promotion of cell motility, migration and adhesion, regulation of matrix metalloproteinases leading to basement membrane degradation (12), and cell survival through inhibition of anoikis (13). Data obtained using cell lines has implicated CCR7 in breast cancer spread to the lymph nodes (14), and in human breast cancer its role was inferred from retrospective studies on archived tumor tissues (15). High CCR7 promotes breast cancer via stem-like cells 4 expression levels of CCR7 were also correlated with higher grade and occurrence of secondary tumors, and poor prognosis (16,17).…”
Section: Introductionmentioning
confidence: 99%